Povratak otpisanih (Epizoda 01) - Povratak . The Return of “The Written Off”, Episode 01 - The Return - Đorđević, Aleksandar (RTV Beograd, 1976)
This 13-part sequel to the same-length TV-series made two years earlier, managed to acquire legendary status and stands out as one of the best examples of Yugoslav WWII movies. The sequel follows the successful pattern of its predecessor and focuses on the same group of characters – mainly Prle and Tihi, two Belgrade members of the communist resistance. The only difference is the time period as the new series shifts from the beginning of the occupation towards the end of the war, with the first episode beginning in the summer of 1944. As victorious partisan forces close in on the city, Prle, Tihi and Joca now must continue their underground work in order to prepare for the liberation of the city. In the first episode Prle and Tihi are on their latest mission: to take a radio transmitter into Belgrade, still under Nazi occupation, and set up a communication post. They join forces with postman Joca, their old acquaintance and moody radio-operator. As always, they succeed in the end and establish a new radio link with the partisans.